Visceral sensitivity index of patients with irritable bowel syndrome after COVID-19 infection - Iana Yu. Feklina; Marina G. Mnatsakanyan; Alexander P. Pogromov; Olga V. Tashchyаn (ZAO "Consilium Medicum", 2022)
Aim. To perform comparative analysis of visceral sensitivity index (VSI) of patients with previously diagnosed irritable bowel syndrome (IBS) and of patients with IBS symptoms after COVID-19 infection. Materials and methods. The study was carried out on the basis of University Clinical Hospital №1; 200 patients with COVID-19 infection were examined. Selection criteria were the recommendations of the Rome Consensus IV (2016). Fourteen patients met the criteria for IBS (Rome IV). Forty patients with a verified diagnosis of IBS before the COVID-19 pandemic (Group 2) were selected as a comparison group. The control group included 50 healthy respondents (group 3). Group 1 included 14 patients; Group 2 included 40 patients (54 patients in total): 37 women and 17 men. The control group included 50 patients: 23 men and 27 women. VSI was estimated in the studied groups. Results. No statistically significant difference of VSI index (p0.05) was revealed while comparing two studied groups (group 1 and group 2). In group 1 and group 2 the mean values of VSI were 24.575.47 and 33.982.55 respectively. Absence of significant differences allows to assume from the position of biopsychosocial model that the patients were initially predisposed to IBS development. Conclusion. A new coronavirus infection is one of the triggers for the development of IBS 6 months after COVID-19 infection.